Modelo de distanciamento controlado: Quais são as medidas adotadas no RS no combate à Covid-19 (Mundo Livre: Revista Multidisciplinar, 2021)
Covid-19 shows itself as a difficulty to be tackled at different levels, and it mainly needs public management actions. Because of this, the present study seeks to identify how the evolution of coping with the Covid-19 pandemic takes place, based on the controlled distance model adopted by the State of Rio Grande do Sul. Thus, from the institution of flags, which had different colors, the State demonstrated different classifications during the evaluation weeks, where from September 2020, the co-management system was instituted, which allowed the municipalities to institute measures, which caused a change in the actions taken. Therefore, this measure proved to be extremely important for the control of the pandemic, providing support for more effective actions, and the risk of contamination tends to vary, requiring greater control of the spread of the disease and the circulation of people.